A Systematic Review of Educational Interventions and Their Impact on Empathy and Compassion of Undergraduate Medical Students - Menezes, Prianna; Guraya, Salman Y.; Guraya, Shaista Salman (Frontiers in Medicine, 2021)
Abstract Introduction A compassionate and patient-centred care leads to improved clinical outcomes. Promoting empathy and compassion of medical students is a forerunner of their wellbeing, emotional stability, and a patient-centred care. However, there is slender evidence about best educational interventions that can inculcate empathy and compassion skills. Our objective was to conduct a systematic review of research evaluating the associations between spectrum, effectiveness, frequency of teaching modalities and their outcomes on compassion and empathy to highlight best practices. Methods We searched the Web of Science, PubMed, Scopus, and EBSCO Host on 22nd July 2020. We adapted our search strategy from a previously published systematic review on education for compassion and empathy. Selected studies were required to have used unique educational interventions for promoting empathy and compassion of medical students. The research questions were based on Participants (medical students), Intervention (empathy and/or compassion related teaching), Comparison and Outcome. Results We analysed 24 articles from the initial yield of 2,861. Twenty-two were quantitative studies with a mean of 12.8 on MERSQI. Twelve were randomized controlled trials while 5 measured outcomes with single group pre- and post-tests. There was no association found between duration, frequency and complexity of an educational intervention and its effectiveness. Twenty used multimodality curricula, and of those 18 reported statistically significant positive improvement in empathy, while 3 of 4 single modality were effective. Only three studies looked for long-term effects of educational interventions. Fourteen studies evaluated Kirkpatrick’s level one (self-reported knowledge), 2 level three (behaviour), and 6 level four (patient outcomes). We identified six major educational constructs of teaching empathy and compassion; communication, mindfulness, early clinical exposure, technology-enhanced learning, comics and arts and culture. Discussion Our review couldn’t identify a standard teaching construct in place and highlighted that different teaching tools carry similar impact in promoting compassion and empathy and a sustainable program rather than a single training activity is essential. Keywords; Compassion; Empathy; Medical students; Communication skills; Mindfulness; Technology-enhanced learning.